2020
DOI: 10.1093/occmed/kqaa187
|View full text |Cite
|
Sign up to set email alerts
|

Doctors’ attitudes to patient occupation information in four hospital specialties

Abstract: Background Although we do not know how often doctors enquire about their patients’ work, evidence suggests that occupation is often not recorded in clinical notes. There is a lack of research into doctors’ views on the importance of patient occupation or their educational needs in this area. Aims To assess doctors’ attitudes to using patient occupation information for care-planning and to determine doctors’ need for specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…In addition we had a good response rate across all medical staffing groups within the specialty. Furthermore, our findings reflect those found from previous work in other specialties such as obstetrics and gynaecology [ 11 ]. This suggests that our collective insights may be generalisable to other surgical specialties who provide care to the working age population.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition we had a good response rate across all medical staffing groups within the specialty. Furthermore, our findings reflect those found from previous work in other specialties such as obstetrics and gynaecology [ 11 ]. This suggests that our collective insights may be generalisable to other surgical specialties who provide care to the working age population.…”
Section: Discussionsupporting
confidence: 91%
“…An earlier study also identified a lack of, and desire for, OH training among doctors working in other specialties (namely, cardiology, gynaecology and obstetrics, oncology and orthopedics) which was also associated with feeling less competent and skilled discussing work outcomes with patients. Moreover, they found a similar discrepancy between the number of doctors from other specialties who consider it important to enquire about occupation and doing so in clinical practice [ 11 ]. Collectively these results suggest that non-OH doctors have a perference for focusing on their own specialty area during patient consultations rather than take into consideration broader factors such as the impact of health on work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, large percentages of different specialty physicians agreed only on the importance of taking an occupational history from patients, as in the current study. 18,27,28 However, a lower percentage agreed when it came to their opinion on their role in detecting occupational diseases or the importance of knowing if the patient's disease has an occupational origin. This may reflect their low general knowledge and interest in occupational health as medical students, as Bhardwaj et al 29 explained.…”
Section: Knowledge and Attitude Of Physicians Toward Occupational Dis...mentioning
confidence: 99%